Silicon and salicylic acid in the physiology and yield of cotton - Barros, Thais Chagas [UNESP] (2019)
Silicon (Si) and salicylic acid (SA) foliar applications can benefit cotton yield especially if there is stress during cultivation. The objective of this study was to evaluate the foliar application of Si and SA on the photosynthetic variables and cotton yield. The experimental design used was randomized complete block, constituted by Si foliar application in potassium and sodium balanced silicate form (0 and 3.6 g L-1 of Si) and SA (0 and 210 mg L-1). The treatments were applied in three leaf sprays during the reproductive stage that coincided with water stress in tillage. Therefore, the Si foliar application associated with SA favors the physiological variables, increasing the photosynthesis, stomatal conductance and water use efficiency reflecting on the increase of cotton yield.